Trends of Unnatural Deaths in Allahabad, Uttar Pradesh - Kaul, Archana; Rai, Rajesh Kumar; Srivastava, Prem Chandra; Agarwal, Priyanka; Rahat, Faraz; Sinha , U S (Journal of Indian Academy of Forensic Medicine, 2016)
Pattern of unnatural deaths is a reflection of the prevailing social set up and mental health status  of the population. Periodic evaluation of trends of unnatural deaths may provide valuable data to adopt  effective preventive measures in this respect. The aim of this study is to find out prevalent pattern of  unnatural deaths in the local society throughout the year and how it is affected by age, sex, habitat,  marital status and season. This study was conducted during March 2014 to March 2015 in Department of  Forensic Medicine and Toxicology, Moti Lal Nehru Medical College, Allahabad. Out of 2958 post-mortem  cases, 2690 (90.94%) were unnatural deaths. 1748 (64.98%) victims were male and remaining 942  (35.02%) were female. Married 2372 (88.18%) cases outnumber unmarried 318 (11.82%). Accidental  deaths accounted for 1648 (61.26%) cases, suicidal deaths for 457 (16.98%) and alleged homicidal  deaths for 275 (10.22%) cases. Maximum deaths 641(23.83%) were observed in age group 25-35 years  in both sexes. Highest incidence was observed in rainy season and least (603) in autumn.
Keywords: Unnatural deaths; Accidental deaths; Seasonal trend; Unmarried; Suicidal